PKM Pendampingan Dan Pelatihan Sistem Perizinan, Digital Branding, Packaging, Dan Digital Marketing Produk UMK Roti Bakar Nax Di Distrik Heram - Arif Budiman, Eren; Fitrianita, Ika; Sandhy Pustap, El Shaddai; Pawan, Elvis (LPPM Universitas Pekalongan, 2025)
Roti Bakar Nax is one of the Micro, Small, and Medium-Sized Enterprises (MSMEs) in Jayapura City. It is owned and run by a group of young Nabire residents who are passionate about business. They began operating this business with very little money, using funds from the town and having very little experience with entrepreneurship. The purpose of this community service project was to assist business actors in boosting the economy. One method is to sell business items using information technology, process business permits to ensure legal protection for a company, and optimize product packaging design to improve a company's reputation and draw in clients. The growth of Roti Bakar Nax in Jayapura City has benefited from this scheme. Effective financial bookkeeping and sales reporting using an information system, brand identity and storytelling strategies, product packaging design optimization, business permits, and digital marketing-based promotional strategies through creative video content on Instagram and TikTok were all areas where business owners showed improved comprehension